2016
DOI: 10.1515/sjph-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Unmet Needs Among Slovenian Old Population

Abstract: BackgroundPopulation ageing has significant effects on societies. The organization of care for dependent old people is one of the key issues for ageing societies. The majority of care for homebound dependent old people in Slovenia is still performed by informal carers, even though the use of formal services has been increasing over the last 20 years. The proportion and characteristics of people with unmet needs are important for the development of long term care social policy.MethodThe SHARE (Survey of Health,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Disparities which were observed between rural and urban settlements are not surprising, as they are observed in other countries as well ( 15 , 26 , 29 , 31 , 32 , 33 , 35 ). Financial constraints most likely enhance lower availability of services in rural areas and higher probability of having unmet needs ( 35 ). Informal care is related to the lack of financial resources, while the usage of formal services is often related to the financial status of care recipients and their families ( 34 ).…”
Section: Discussionsupporting
confidence: 60%
“…Disparities which were observed between rural and urban settlements are not surprising, as they are observed in other countries as well ( 15 , 26 , 29 , 31 , 32 , 33 , 35 ). Financial constraints most likely enhance lower availability of services in rural areas and higher probability of having unmet needs ( 35 ). Informal care is related to the lack of financial resources, while the usage of formal services is often related to the financial status of care recipients and their families ( 34 ).…”
Section: Discussionsupporting
confidence: 60%
“…There are also distinct differences in the accessibility of services for persons in the institutional care and persons in homecare as well as high regional differences in the availability of these services. Furthermore, the estimated number of people with severe unmet needs suggests that there are significant opportunities for social policy changes and development of new public and private services for older people in need, as well as for the integration of fragmented LTC (Hlebec, 2016a). These statements confirm the ascertainment that there exists a need for development of additional type of the formal homecare services for the elderly in Slovenia.…”
Section: Discussionmentioning
confidence: 62%
“…The authors have proclaimed informal care to be the most wide-spread form of care for the older people in Slovenia. In contrast, another study by Hlebec et al (2016a) revealed that, despite the efforts toward care for dependent elderly in Slovenia, there are still a proportion of older people with several needs for care, which are being unmet. Furthermore, the research by Hlebec et al (2014) showed that municipalities in Slovenia differ dramatically in the availability of care for the older people.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, PC is often restricted to physical symptom relief in the terminal phase, including emergency visits by the GP, transfers and unplanned hospital admissions ( 11 ). Moreover, 4% of the elderly Slovenian population have severe limitations, for which they do not receive any care ( 12 ). Without a universally accepted definition of ‘early’ palliative care, the dilemma arises of marking the right moment to start anticipatory PC alongside or instead of disease-oriented care in the advanced stages of chronic diseases ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%